Development of Multifunctional Pet-Human Nightstand (CatNook 2.0) - Koh, Ming Jia; Md Rawi, Muhammad Firdaus (Research in Management of Technology and Business, 2026)
This study focuses on the design and development of a multifunctional pet-human nightstand intended for cat owners living in modern Malaysian homes. The objectives of this research were to identify key design criteria, propose design solutions, and construct a functional prototype. Data collection was conducted through two methods: in-depth interviews with three long-term cat owners in Malacca with over thirty years of experience, and a Google Forms survey completed by 280 respondents in Melaka. The combined qualitative and quantitative findings revealed essential design criteria, including easy-to-clean materials, a bottom-positioned cat resting compartment, adequate ventilation, changeable scratching mats, the use of rubberwood, and a minimalist visual style. Based on these criteria, 36 thumbnail sketches, 6 ideation sketches, and 42 design development drawings were produced, resulting in three final design alternatives. Design 3 was chosen as the preferred option by survey respondents. Technical drawings were produced using SolidWorks software, and a 1:8 mock-up was constructed to evaluate form and functionality. The final full-scale prototype, CatNook 2.0, was developed using solid rubberwood, epoxy resin, optical fibre lighting, and traditional joinery. The prototype measures 680 mm in height, 560 mm in length, and 500 mm in width, featuring a motion-activated fibre-optic lighting tabletop, a removable tambour-door drawer, and a ventilated cat resting nook. The results demonstrate that a systematic and user-centred design process can effectively translate user needs into an integrated furniture solution that enhances both human convenience and feline comfort. This study concludes that multifunctional pet-human furniture can address common issues of clutter, underutilized pet products, and spatial inefficiency. Recommendations for future development include improving the lighting system, exploring modular variations, and conducting long-term user testing to further refine functionality.